The evolution of convergence net added value per conventional worker (euro/worker) in the countries of the European Union, over the period 2007-2021 - Raluca-Alexandra Rădoi; Manea Drăghici; Emilian Merce (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
Apart from the aspects of legislative and institutional convergence, we believe that convergence, more than 14 years after Romania's accession to the EU, can also be measured quantitatively through statistical indicators. For the study, the indicator of the value of net agricultural production per worker (VAN) was taken in the countries of the European Union, for the period 2007-2021. The paper is divided into three sections, of which, in the first section, the evolution of the VAN per agricultural worker is described, in the second, the convergence tendency of the VAN indicator per agricultural worker is analyzed, to fall within the confidence limits of the EU average, for different degrees of probability and in the last section of the paper the evolution of the VAN convergence per agricultural worker is presented, through the value and percentage differences of the net added value per conventional agricultural worker compared to the average of the European Union, for the period 2007-2021. The VAN/AWU analysis, by comparing the growth rates through the value and percentage dispersion around the average and by the statistical positioning of the countries, against the intervals of the confidence limits of 95%, 99% and 99.9%, demonstrates that in the analyzed period 2007 -2021, has increased in value in all countries but they did not have a tendency to converge, respectively to reduce the discrepancies that exist between the countries of the European Union.
Keywords: Q19; O47; 330; convergence; value of net agricultural production; probability; rhythm; confidence limits